Heart of public service. Our People - Public Service Division, Prime Minister's Office; Singapore. Prime Minister's Office. Public Service Division (Singapore : Public Service Division, Prime Minister's Office, 2015)
History of public services in Singapore.
[1] Our institutions -- [2] Our people.
Includes index.
In English.
Keywords: Civil service -- Singapore -- History; Public administration -- Singapore -- History